2015
DOI: 10.21276/ambi.2015.02.1.ra05
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and Conservational Status of Avifauna in Bastar Plateau of Chhattisgarh, India

Abstract: The present study aims at preparing a consolidated account on the avifaunal composition of Bastar plateau by compiling the information given in the past literatures and observations gathered during the present f ield work. Thus, a total of 304 species of birds belonging to 194 genera under 63 families have been listed from the area including f ive birds recorded for the f irst time from Central India. Moreover, the list includes 15 Globally Threatened birds comprising three Critically Endangered, one Endangere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…In the present study from the selected site, Family Muscicapidae was found to be very rich with the highest relative diversity (RD) index (RD value=13.7) as shown in (Fig: 3). [11,19,24,25] also found the Family Muscicapidae to be dominant in their studies. Red-vented bulbul, Blue Rock pigeon, Common tailorbird, Ashy prinia, Rose-ringed parakeet, Little brown dove, Purple sunbird, Jungle babbler, Coppersmith barbet and Red-wattled lapwing were found to be the most common birds during the present study as were also found in the studies of [3,16,21,26,27].…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…In the present study from the selected site, Family Muscicapidae was found to be very rich with the highest relative diversity (RD) index (RD value=13.7) as shown in (Fig: 3). [11,19,24,25] also found the Family Muscicapidae to be dominant in their studies. Red-vented bulbul, Blue Rock pigeon, Common tailorbird, Ashy prinia, Rose-ringed parakeet, Little brown dove, Purple sunbird, Jungle babbler, Coppersmith barbet and Red-wattled lapwing were found to be the most common birds during the present study as were also found in the studies of [3,16,21,26,27].…”
Section: Resultsmentioning
confidence: 88%
“…As these 10 species of migratory birds were only recorded during the winter season they were designated as winter migratory birds as studied by [17]. One species, Alexandrine parakeet was found to be in the Near Threatened category of IUCN (International Union for Conservation of Nature) [18,19].…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, out of 50 new records, 06 species are the f irst record from Central India. The current 50 new avifauna species adds to our previous records Chandra (2015) and the updates avifauna diversity of the Bastar district to a f igure of 319 species. All the 50 species recorded from Bastar district indicates the habitat needs of these birds.…”
mentioning
confidence: 82%
“…However, the species was unreported from central India (Chandra & Singh, 2004, Chandra et al, 2015. This note describes the occurrence and first reporting of the species from Chhattishgarh at Dalpat Sagar Lake in Jagdalpur (19° 05'55.5'' N,82° 00'46.0''' E; …”
Section: Introductionmentioning
confidence: 91%